HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KEAKTIFAN BELAJAR SISWA SMPN 03 KOTA JAMBIHUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN KEAKTIFAN BELAJAR SISWA SMPN 03 KOTA JAMBI - Marliana, Nurwahidah; Sofyan , Hebra; Niki, Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
activities, as indicated by students’ reluctance to ask questions, inability to answer teachers’ questions, frequent requests to leave the classroom, late assignment submission, chatting, playing during class, and failure to complete assigned tasks. The study aimed to determine the relationship between emotional intelligence and students’ learning activity. Learning activity refers to students’ intellectual and emotional involvement in the learning process and is considered an important factor in achieving learning success. This research employed a quantitative approach with a correlational design. The population consisted of 206 students, and a sample of 140 students was selected using random sampling techniques. Data were collected through questionnaires, supported by observations and interviews with guidance and counseling teachers. The questionnaire was developed using a Likert scale and had met validity and reliability requirements. Data were analyzed using a correlation test. The results showed a significance value of 0.000 and a correlation coefficient of 0.706. Since the significance value was lower than 0.05 (0.000 < 0.05), a significant relationship was found between emotional intelligence and learning activity. The correlation coefficient of 0.706 indicates a high level of correlation. Therefore, it can be concluded that emotional intelligence has a strong relationship with students’ learning activity.